NPHP4 Variants Are Associated With Pleiotropic Heart Malformations - French, Vanessa M.; van de Laar, Ingrid M.B.H.; Wessels, Marja W.; Rohe, Christan; Roos-Hesselink, Jolien W.; Wang, Guangliang; Frohn-Mulder, Ingrid M.E.; Severijnen, Lies-Anne; de Graaf, Bianca M.; Schot, Rachel; Breedveld, Guido; Mientjes, Edwin; et al. (Circulation research, 2012)
RATIONALE:Congenital heart malformations are a major cause of morbidity and mortality, especially in young children. Failure to establish normal left-right (L-R) asymmetry often results in cardiovascular malformations and other laterality defects of visceral organs. OBJECTIVE:To identify genetic mutations causing cardiac laterality defects. METHODS AND RESULTS:We performed a genome-wide linkage analysis in patients with cardiac laterality defects from a consanguineous family. The patients had combinations of defects that included dextrocardia, transposition of great arteries, double-outlet right ventricle, atrioventricular septal defects, and caval vein abnormalities. Sequencing of positional candidate genes identified mutations in NPHP4. We performed mutation analysis of NPHP4 in 146 unrelated patients with similar cardiac laterality defects. Forty-one percent of these patients also had laterality defects of the abdominal organs. We identified 8 additional missense variants that were absent or very rare in control subjects. To study the role of nphp4 in establishing L-R asymmetry, we used antisense morpholinos to knockdown nphp4 expression in zebrafish. Depletion of nphp4 disrupted L-R patterning as well as cardiac and gut laterality. Cardiac laterality defects were partially rescued by human NPHP4 mRNA, whereas mutant NPHP4 containing genetic variants found in patients failed to rescue. We show that nphp4 is involved in the formation of motile cilia in Kupfferʼs vesicle, which generate asymmetrical fluid flow necessary for normal L-R asymmetry. CONCLUSIONS:NPHP4 mutations are associated with cardiac laterality defects and heterotaxy. In zebrafish, nphp4 is essential for the development and function of Kupfferʼs vesicle cilia and is required for global L-R patterning.